A gente vive é rodando : movimentos quilombolas que educam com os saberes da confluência - Fernanda Cristina de Oliveira e Silva (2020)
This doctoral dissertation proposes to describe knowledge practices between quilombola masters, dialoguing with Nilma Lino's thesis on the Black Movement as a subject of knowledge and an educating agent (2017). I intend to converge with this proposition, describing quilombola experiences marked by movements that have, among its main aspects, the teaching- learning process of coexisting with the diversity as a cause and effect of collective actions. I argue that, different from the image of isolation that the hegemonic common sense insists on suggesting, it is taught and learned to 'live quilombola', moving through different territories. Rotating and crossing borders - physical, ontological, epistemological - as forms of counter-colonization. The quilombolas who work with me on this thesis are practitioner thinkers with whom I have lived since 2011 - when a journey begins between my university career and the communities of terreiros and quilombos. The form of the text is ethnographic and intermittent, alternating passages that show trajectories of Silvio de Siqueira (Mestre Badu, from the Matição quilombo / Jaboticatubas-MG), Mametu Muiande and Makota Kidoiale (Efigênia Maria da Conceição and Cássia Cristina da Silva from Kilombu Manzo Ngunzo Kaiango/BH-MG), Antônio Bispo dos Santos (Nêgo Bispo, from the Saco Curtume quilombo/PI) and Mestre Arnaldo de Lima (Naldinho, from the Custaneira quilombo/PI). The descriptions accompany an effort to conceptualize their experiences as 'wisdoms of circularity' that converge to a 'pedagogy of borders'.